Semantic rivalry between affixes: the case of Portuguese nominalisers - Rodrigues, Alexandra Soares (2015)
In Portuguese there are different suffixes that permit us to construct event deverbal nouns. Those affixes may adjoin the same verbal base.Albeit deriving event nouns, the meanings of the derivatives of these suffixes are slightly different. We intend to contribute to the understanding of the mechanisms that are involved in affix semantic rivalry, specifically to the knowledge of the semantic features of the verbal base that are sensitive to the semantics of each affix.